Concepto de psicoterapia en psicología clínica (2010)
ABSTRACT: This article presents a literature review of the concept psychotherapy in Clinical Psychology. A large sample of articles and documents are analyzed in order to describe the historical background that gave rise to the notion of psychotherapy in Psychology. Special emphasis has been given to the conceptualization of psychopathology proposed by the more important Psychological Schools: Dynamic, Cognitive, Behavioral, Humanist, and Systemic.